2015
DOI: 10.5194/acp-15-2825-2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary and secondary wood combustion products generated under different burner loads

Abstract: Abstract. Residential wood burning contributes to the total atmospheric aerosol burden; however, large uncertainties remain in the magnitude and characteristics of wood burning products. Primary emissions are influenced by a variety of parameters, including appliance type, burner wood load and wood type. In addition to directly emitted particles, previous laboratory studies have shown that oxidation of gas-phase emissions produces compounds with sufficiently low volatility to readily partition to the particles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 82 publications
15
117
3
4
Order By: Relevance
“…WOOA mass spectrum exhibited elevated contributions of A. Vlachou et al: Advanced source apportionment of carbonaceous aerosols , 73, 85 and 99, respectively) to the one coming from oxygenated products from a wood-burning experiment (Bruns et al, 2015) was found. The recovery of this factor manifested high values (Table 2) and consisted mainly of fine-mode particles (Fig.…”
Section: Offline Ams Analysis Results: Factor Interpretationmentioning
confidence: 99%
“…WOOA mass spectrum exhibited elevated contributions of A. Vlachou et al: Advanced source apportionment of carbonaceous aerosols , 73, 85 and 99, respectively) to the one coming from oxygenated products from a wood-burning experiment (Bruns et al, 2015) was found. The recovery of this factor manifested high values (Table 2) and consisted mainly of fine-mode particles (Fig.…”
Section: Offline Ams Analysis Results: Factor Interpretationmentioning
confidence: 99%
“…Primary and aged emissions were characterized using a suite of instrumentation. This included a TAG-AMS (Aerodyne Research Inc.) for the online speciation of the OA particle mass, an Aethalometer (Magee Scientific Aethalometer model AE33) (Drinovec et al, 2015) for the quantification of the equivalent black carbon (BC) concentration, a HR-ToF-AMS (Aerodyne Research Inc.) for the bulk-condensed chemical composition of the non-refractory fraction of the aerosol, and a Proton Transfer Reaction -Time of Flight -Mass 15…”
Section: Set Upmentioning
confidence: 99%
“…Its ubiquity and abundance (Waked et al, 2014;Bonvalot et al, 2016;Maenhaut et al, 2016) have been used to demonstrate the significant contribution of biomass burning to the total organic aerosol source globally (Robinson et al, 2006;Gelencsér et al, 2007;Puxbaum et al, 2007;Stone et al, 2010;Crippa et al, 2013). 20 The concentration of organic aerosol (OA) particle mass has been documented to increase up to 7 times during photochemical aging (Grieshop et al, 2009;Heringa et al, 2011;Ortega et al, 2013;Bruns et al, 2015;Tiitta et al, 2016), however, the chemical composition of this secondary organic aerosol (SOA) produced remains uncertain. Multiple studies investigated the oxidation of specific gas-phase precursors commonly emitted by biomass burning, namely methoxyphenols (Net et al, 2011;Lauraguais et al, 2012;Yee et al, 2013;Lauraguais et al, 2014), but few have specifically addressed the 25 aging of specific biomass burning tracers in the particle phase (Hennigan et al, 2010;Kessler et al, 2010;Lai et al, 2014), and so far, only Fortenberry et al (2017) have attempted characterizing the aged chemical fingerprint of biomass burning emissions at the molecular level by means of a Thermal Desorption Aerosol Gas Chromatograph (TAG) connected to a Potential Aerosol Mass (PAM) flow reactor.…”
Section: Introductionmentioning
confidence: 99%
“…These samples did not only include the primary aerosol, but also two different levels of ageing, i.e. after simulated ageing in a smog chamber for 1 h (equivalent to an OH dose of 10 7 cm −3 h) and 4 h (OH dose 3×10 7 cm −3 h) (Bruns et al, 2015(Bruns et al, , 2016. Additionally, filter samples collected during cooking experiments were analysed (Klein et al, 2016a, b).…”
Section: Sample Collection and Other Chemical Analysesmentioning
confidence: 99%